Digital signal processing : spectral computation and filter design - Chen, Chi-Tsong (The Oxford Series in Electrical and Computer Engineering Ser., 2001)
"Digital Signal Processing features careful definitions of all terminology and a wealth of examples and problems. All numerical examples and most end-of-chapter problems are simple enough to be solved analytically by hand; these results can then be compared with the computer-generated solutions. MATLAB is an integral part of the text."--BOOK JACKET.